Masterclass. New First Certificate. Teachers Book - Haines, Simon and Stewart, Barbara (Oxford Oxford University Press, 1997)
This is the Teachers Book to the New First Certificate Masterclass, which is an effective exam preparation course for the revised Cambridge First Certificate in English (1996 revision). The course combines a systematic review of the language tested with extensive exam training.
Keywords: English Practice